Lead nitroprusside: A new precursor for the synthesis of the multiferroic Pb2Fe2O5, an anion-deficient perovskite - Gil, D.M. (2013)
Fil: Nieva, G. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina